A class of Gauss curvature flows and its applications to an even dual Orlicz–Minkowski type problem. (May 2022) - Wu, Di; Tu, Qiang; Xie, Siyuan
Abstract: In this paper, we consider a class of anisotropic Gauss curvature flows and obtain the long-time existence. As an application, an existence result of the even solution has been obtained for a class of Monge–Ampère type equations, which associated a dual Orlicz–Minkowski type problem for the even measure.